Pengaruh Penyaluran Dana Zakat dan IPM Terhadap Kemiskinan Provinsi Jambi Tahun 2010-2021 - Martaliah, Nurfitri; Anita, Efni; Naufal ramli, Luthfi; Rahman, Fuad (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The high distribution of zakat funds, the human development index can affect the level of poverty in Jambi Province. The purpose of this study is to find out how the influence of the distribution of zakat funds and the human development index on poverty. The variables used are the distribution of zakat funds and the human development index on poverty in Jambi Province in 2010-2021. The object of this research is Jambi Province which is registered in BAZNAS and BPS for the 2010-2021 period. The method used is multiple linear regression. The results of this study indicate that simultaneously the distribution of zakat funds and the human development index variables have a significant effect on the poverty rate in Jambi Province. Partially, the distribution of zakat funds has no significant effect on poverty. Meanwhile, the human development index has a significant effect on the poverty rate in Jambi Province. The value of the coefficient of determination (R2) is known that the value of the coefficient of determination is 0.948725. This shows that the dependent variable (poverty level) can simultaneously be explained by the independent variables (zakat fund distribution and human development index) of 94.87% while the remaining 5.13% is explained by other factors outside the variables studied. Keywords: Distribution of zakat funds, human development index, and poverty level